Alterations in gut microbiota and elevated serum bilirubin in primary biliary cholangitis patients treated with ursodeoxycholic acid. (9th December 2021) - Han, Weijia; Huang, Chunyang; Zhang, Qi; Tao, Shuhui; Hu, Xiaomin; Xu, Jianguo; Jiang, Ronglong; Xu, Bin; Liu, Yanmin; Hou, Jinlin
Abstract: Background: The prognosis of primary bile cholangitis (PBC) is linked to gut microbiota dysbiosis. This study investigated the association between the gut microbiome and elevated total bilirubin (TB) level in PBC patients treated with ursodeoxycholic acid (UCDA). Methods: A total of 47 PBC patients with 12 months of UCDA treatment were enrolled. Patients were divided into the TB (+) (TB>1× upper limit of the normal range [ULN]; n = 20) and TB(−) (TB≤1× ULN; n = 27) groups. Stool and serum specimens were collected, and microbiota composition and functional characteristics in the 2 groups were evaluated by 16S RNA gene sequencing and bioinformatic analysis. Results: Bacterial diversity was lower in the TB(+) group than in the TB(−) group, although there was no significant difference in bacterial community profile. The phylum Saccharibacteria showed differential abundance in the 2 groups. Meanwhile, the TB(−) group had lower abundance of the Gemmiger, Blautia, Anaerostipes and Coprococcus genera than the TB(+) group, whereas Holdemania was absent. The abundance of Gemmiger formicillis and Coprococcus eutactus was positively correlated with that of Faecalibacterium prausnitzii, while Blautia, Anaerostipes and Coprococcus were negatively correlated with total bile acid level. Conclusion: TB level in PBC patients treated for 12 months with UCDA is associated with a distinct gut microbiome profile.